Rekayasa Perangkat Lunak Pengelolaan Data Alumni Stt Indonesia Tanjungpinang - Saharudin; Hendi Setiawan (Jurnal Bangkit Indonesia, 2020)
Every college must have alumni information data after graduating, so far the data collection is only done by taking notes in printed documents, resulting in data management that cannot be done quickly and still often has errors and is difficult to update, this problem can be overcome with a the method that is developing is the programming system. One of them is programming in the form of software. With this information management system software, it is expected to help manage school alumni data.